The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.21273/horttech.13.1.0090
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Reflective Film and Ethephon to Improve Red Skin Color of Apples in the Mid-Atlantic Region of the United States

Abstract: Replicated studies were conducted from 1996 to 1999 to evaluate the effect of a metalized reflective film (RF) on red color development in several apple (Malus ×domestica) cultivars that often develop poor to marginal color in the mid-Atlantic growing region. Film was applied to the orchard floor in the middle between tree rows or under the tree beginning 5 to 7 weeks before the predicted maturity date. Light reflected into the canopy from the RF wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
19
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 11 publications
3
19
0
1
Order By: Relevance
“…Training systems (Hampson et al, 2004), growth regulators (Miller, 1988), plant nutrition (Williams and Billingsley, 1974), and reflective films (Layne et al, 2001(Layne et al, , 2002Miller and Greene, 2003) are techniques that improve fruit quality entirely or in part by improving light penetration into the tree canopy. Reflective films have been developed to reflect narrow bands of light (Kasperbauer, 1999) or the entire spectrum using white (Grout et al, 2004) or metallized films (Layne et al, 2001(Layne et al, , 2002Miller and Greene, 2003). Reflective films increase red color development in apple, primarily in the lower half of the canopy (Moreshet et al, 1975) and may alter date of fruit maturation (Miller and Greene, 2003).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Training systems (Hampson et al, 2004), growth regulators (Miller, 1988), plant nutrition (Williams and Billingsley, 1974), and reflective films (Layne et al, 2001(Layne et al, , 2002Miller and Greene, 2003) are techniques that improve fruit quality entirely or in part by improving light penetration into the tree canopy. Reflective films have been developed to reflect narrow bands of light (Kasperbauer, 1999) or the entire spectrum using white (Grout et al, 2004) or metallized films (Layne et al, 2001(Layne et al, , 2002Miller and Greene, 2003). Reflective films increase red color development in apple, primarily in the lower half of the canopy (Moreshet et al, 1975) and may alter date of fruit maturation (Miller and Greene, 2003).…”
mentioning
confidence: 99%
“…Reflective films have been developed to reflect narrow bands of light (Kasperbauer, 1999) or the entire spectrum using white (Grout et al, 2004) or metallized films (Layne et al, 2001(Layne et al, , 2002Miller and Greene, 2003). Reflective films increase red color development in apple, primarily in the lower half of the canopy (Moreshet et al, 1975) and may alter date of fruit maturation (Miller and Greene, 2003). Layne et al (2001Layne et al ( , 2002 measured increased ultraviolet A radiation (UVa) (330-400 nm), photosynthetically active radiation (PAR) (400-700 nm), and near-infrared radiation (NIR) (700-1100 nm) reflection from a reflective film and a resulting increased air temperature within the canopy and found that the red light/far-red light ratio (R/FR) of the reflective film was similar to incoming radiation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Reduction in juneberry growth was attributed to the stress incited by the warm microclimate from the dark-colored, reflective landscape fabric. Miller and Greene (2003) reported that reflective films placed at orchard floors can increase plant canopy temperatures up to 19.8°F compared with plots without reflective film. St-Pierre and Tulloch (2002) reported greater juneberry growth when grown in black plastic compared with those grown in wood chips or without mulch, even though plants suffered from sun scald.…”
Section: Resultsmentioning
confidence: 99%